INTEGRASI SISTEM REKAM MEDIS ELEKTRONIK PADA FASYANKES UNTUK MENDUKUNG PROGRAM EKOSISTEM DIGITAL KESEHATAN NASIONAL - Puad, Lailyn; William Gading, Patrick; Limia Budiarti, Rike (JURNAL AKADEMIKA, 2024)
Electronic Medical Records (RME) are important records, which are recorded to describe a patient's medical status in digital or computerized form. One of the goals of this integration program is so that all RME data can be standardized using SNOMED-CT which is an international terminology standard related to clinical terms issued by SNOMED International, including a comprehensive vocabulary of medical concepts, including medical and anatomical conditions, as well as medical tests, treatments, procedures, ICD-10, ICD-9 CM and LOINC.